INVESTIGATION OF SURFACE ROUGHNESS OF CARBON STEEL MACHINED PARTS AFTER NANOSECOND FIBER LASER MARKING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Laser marking with a nanosecond fiber laser is one of the most common ways to permanently mark various engineering materials. The roughness of the machined surface and its observation is essential to evaluate the impact on the contrast of the marking as well. Experimental studies of the roughness obtained as a result of the laser marking, were inspected using a 3D measuring laser microscope OLYMPUS LEXT OLS5100. Analysis of the graphical dependence of the roughness function on the four process parameters: laser power, frequency, speed of marking and step.